MyD88 inhibitor TJ-M2010-5 alleviates spleen impairment and inflammation by inhibiting the PI3K/miR-136-5p/AKT3 pathway in the early infection of Trichinella spiralis - Huifang Bai; Qianqian Dang; Guoliang Chen; Lingfeng Xie; Saining Wang; Ning Jiang; Xiaoxia Wu; Shuyan Zhang; Xuelin Wang (Veterinary Research, 2025)
Abstract Trichinella spiralis (T. spiralis) has been reported to induce inflammation, which can cause immune system dysregulation. Myeloid differentiation primary response gene 88 (MyD88) is implicated in inflammation signalling pathways. TJ-M2010-5 is a novel MyD88 inhibitor with remarkable protective effects against several diseases. However, the precise mechanism of TJ-M2010-5’s involvement in spleen impairment and inflammation in the early infection of T. spiralis has yet to be fully elucidated. This study analysed histological, inflammation, and macrophage polarisation of the early T. spiralis-infected mice treated with TJ-M2010-5. MyD88 promoter methylation results showed that the methylation levels in the 5 d group were lower compared to the control group (P < 0.05). Furthermore, the methylation led to an imbalance in anti-inflammatory regulation in the infected mice. After TJ-M2010-5 treatment, spleen impairment was reduced. Sequencing analysis showed that TJ-M2010-5 significantly up-regulated 9 and down-regulated 10 miRNAs compared with the 5 d group. A dual-luciferase reporter assay further revealed that miR-136-5p is involved in the TJ-M2010-5 treatment by targeting AKT3. In RAW264.7 cells, TJ-M2010-5 pre-treatment significantly reversed the M1 polarisation and inhibited nitric oxide (NO) production. LC–MS/MS results showed TJ-M2010-5 was hepatosplenic-targeted. In conclusion, the study demonstrates that TJ-M2010-5 could effectively alleviate spleen impairment and reduce inflammation in mice infected with T. spiralis in its early stages by blocking the activation of PI3K/miR-136-5p/AKT3.